Strategi Pengembangan Wisata Heritage Kya Kya Kembang Jepun sebagai Destinasi Wisata Prioritas Kota Surabaya - Diana Izzati; Fahrurozy Darmawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Kya Kya Kembang Jepun is a heritage area in Surabaya with significant historical and cultural value. However, this area faces challenges in sustainable management, inconsistent policies, and lack of coordination among stakeholders. This study aims to analyze the development strategies for Kya Kya Kembang Jepun as a tourism destination using the 4A framework (Attraction, Amenity, Accessibility, Ancillary) and SWOT analysis (Strength, Weakness, Opportunity, Threat). A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, and documentation from relevant informants. The findings indicate that Kya Kya possesses strong cultural attractions, Chinese culinary offerings, and cultural performances that support its tourism branding. Accessibility is adequate, but improvements in transportation and parking are necessary. Available amenities are satisfactory, but maintenance requires attention. Based on the SWOT analysis, recommended strategies include sustainable revitalization, strengthening inter-agency collaboration, and more targeted digital promotion. With the right strategies, Kya Kya Kembang Jepun has the potential to become a competitive and sustainable heritage tourism icon in Surabaya.